Right to Repatriation of Abandoned Seafarers: A Study in Light of Maritime Labour Convention 2006, and International Covenant on Civil and Political Rights 1966 - Gupta, Mohit (The Age of Human Rights Journal, 2023)
The abandonment of seafarers is one of the major challenges that seafarers onboard vessels may face. In 2022, 1555 seafarers were abandoned on 113 ships. The port state’s role in seafarer abandonment is crucial because it can assist abandoned seafarers by facilitating their repatriation. In practice, however, it has been seen in many cases that the port state of the vessel had restricted the disembarkation of the abandoned crew from the vessel by citing the reason that the vessel cannot be left unmanned. The present study will assess such measures adopted by the port states in light of International Law instruments, including the Maritime Labour Convention, 2006 and the International Covenant on Civil and Political Rights, 1966.